Low Cost Humidity Sensor Based on PANI/PEDOT:PSS Printed on Paper - Morais, Rogerio M. [UNESP]; Klem, Maykel Dos Santos [UNESP]; Nogueira, Gabriel Leonardo [UNESP]; Gomes, Tiago Carneiro [UNESP]; Alves, Neri [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
The production of low cost sensors to monitor environment in some industrial sectors is a current need. In aviculture centers, for example, the concentration of ammonia gas is related to humidity, and it is necessary to control it to avoid contamination. With this need in mind, this paper presents the preparation and characterization of a low cost humidity sensor based on poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and polyaniline fully printed onto paper by a commercial HP printer. Using electrochemical impedance spectroscopy, an equivalent circuit containing resistive and capacitive parameters was proposed. The resistive parameter R1 is related to values of ambient humidity. The R1 values showed a sensitive response of 200% when relative humidity changes 80%, taking 10 min to reach saturation point. Moreover, the device showed good stability when humidity remained constant. These results indicate that the proposed device is suitable for applying as a humidity sensor that costs less than 1 Euro cent.
Keywords: Ink jet printing; PANI; paper based device; PEDOT:PSS; printed humidity sensor